Simulação do desempenho reprodutivo de vacas de corte submetidas a diferentes durações de estação de monta e condições nutricionais - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The beef cattle industry is essential in the development of the national economy, with breeding being the phase of greater importance in the beef chain efficiency. At this phase, among others, two factors are critical and should be taken into account for maximum reproductive performance: duration of the breeding season and the body condition score (BCS). The objective of this study was to test different nutritional conditions, based on body condition score, associated to different breeding seasons. The study was conducted from a simulation model for reproductive performance of beef cows, according to different scenarios. Nutritional conditions were represented by groups LOW (60% cows with BCS 2 and 40% with BCS 3), MEDIUM (20% cows with BCS 2, 60% cows with BCS 3 and 20% with BCS 4) and HIGH (40% with BCS 3 and 60% of cows BCS 4) these conditions were tested for three breeding seasons: with 60, 90 and 120 days of duration. The response variables analyzed were conception rate, calving interval, calving-conception interval and weaning weight of calves. It was observed that extending the length of the breeding season, the greater is the herd conception rate in the first year, but this length can negatively influence the breeding back of the cows in the subsequent years, since the calving-conception interval also increased, as well as the calving interval. The analyzed results are demonstrative data, since there was no statistical analysis. Scenarios simulation can be effective for maximizing productivity with beef cattle. Both the farmer as the technical, are potential users of this tool to evaluate the reproductive performance of the herd, pointing out that the simulation serves as a support method, as it should take into consideration the system as a whole.
Keywords: Bovinocultura de corte; Condição corporal; Estação reprodutiva; Modelagem; Rebanho de cria; Beef cattle; Body condition; Breeding season; Cow/calf operation; Modeling; CNPQ::CIENCIAS AGRARIAS